Tourism Marketing 3.0 on Mangunan Orchad to Create Sustainable Tourism In Yogyakarta - Sulistyo, Agung; Annisa, Rosalina Nur (Stupa, 2021)
The concept of Tourism Marketing 3.0 has been applied by several tourist destinations in the world to attract tourist visits. The indicators used are Technology Change, Political Legal Change, Economic Change, Socio-Culture Change and Market Change. The number of tourist attractions popping up in Yogyakarta encourage managers to set the right strategies and plans so that the tourist attraction of the Mangunan Orchard is increasingly in demand. The purpose of this study is to analyze the application of the concept of Tourism Marketing 3.0 on the tourist attraction of the Mangunan Orchard, in order to attract tourist visits. This research uses a qualitative method with a descriptive approach combined with the concept of Tourism Marketing 3.0 analysis. Data collection in this study uses in-depth interviews, observation, documentary methods, visual material methods, and literature study. The subjects of this study were several people who came from the Department of Agriculture, Food, Maritime Affairs and Fisheries, the Department of Tourism, Managers in the field, as well as several tourists who visited the Tourist attraction of Mangunan Orchard. Based on research that has been done, the results obtained that the tourist attraction of the Mangunan Orchard is not in accordance with the concept of Tourism Marketing 3.0. This is because the attributes used: Technology Change, Political Legal Change, Economic Change, Socio-Culture Change and Market Change have not been fully applied. With these results, the right strategies and programs are needed in applying the concept to attract tourist visits.